Understanding New Consumption Sites of Internet Cafe in Yogyakarta, Indonesia - Tangguh Okta Wibowo; Wening Udasmoro; Ratna Noviani (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
In the Indonesian context, we did not find any previous study on internet cafes that discussed the transformation from warnet to internet cafe. Based on our study in Yogyakarta, we found a new internet cafe style that we did not find in other cities. This study offers a new understanding of analyzing internet cafes that users not only consume a computer to access the internet, but they “consume” space as well. This study aims to explore that transformation and to reveal the expansion of consumption patterns. This study emphasizes the empirical investigation to gather the data. We conducted qualitative in-depth interviews and observations from January to June 2018. We also examined several previous studies about internet cafes to expose a gap that can be extended in this study. Based on findings, we found that the transformation from warnet was a way to survive amid mobile technology. This transformation gives an implication to the new means of consumption. However, the expansion of consumption patterns can be explored from the consumption of space and digital content. Overall, digital content is the new insight to understand that internet cafes are not only a place to copy contents, but this can be seen as a symbol of empowerment to local users. Therefore, internet cafes can be seen as media-industry bottom lines to promote a culture of resistance to digital content without going to the store or going to the cinema.